2022
DOI: 10.1021/acschemneuro.2c00264
|View full text |Cite
|
Sign up to set email alerts
|

Mass Spectrometry-Based Analysis of Serum N-Glycosylation Changes in Patients with Parkinson’s Disease

Abstract: It is urgently needed to find reliable biofluid biomarkers for early diagnosis of Parkinson's disease in order to achieve better treatment. Promising biomarkers can be found in Parkinson's disease-related glycoproteins as aberrant protein glycosylation plays an important role in disease progression. However, current information on serum N-glycoproteomic changes in Parkinson's disease is still limited. Here, we used glycoproteomics methods, which combine the solid-phase chemoenzymatic method, lectin affinity ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 45 publications
0
22
0
Order By: Relevance
“…In a recent N-glycoproteomics-based study, researchers identified an increase in the number of glycans containing core fucose, sialic acid, and bisecting N-acetylglucosamine in the sera of human patients, both at the overall glycan level and at specific glycosites of proteins related to Parkinson’s disease. These proteins include Ceruloplasmin, Haptoglobin, Kininogen-1, Complement Factor H, and Clusterin [ 68 ].…”
Section: N-glycosylationmentioning
confidence: 99%
“…In a recent N-glycoproteomics-based study, researchers identified an increase in the number of glycans containing core fucose, sialic acid, and bisecting N-acetylglucosamine in the sera of human patients, both at the overall glycan level and at specific glycosites of proteins related to Parkinson’s disease. These proteins include Ceruloplasmin, Haptoglobin, Kininogen-1, Complement Factor H, and Clusterin [ 68 ].…”
Section: N-glycosylationmentioning
confidence: 99%
“… 1 Dynamic changes in glycosylation states have been associated with different disease processes, such as cancer, 2 viral infection responses, 3 and Alzheimer’s disease; 4 the extent of the glycosylation could be associated with the disease progression 5 and prognosis. 6 These observed associations indicate that the specific glycosylation states of proteins can be utilized as biomarkers for clinical diagnosis 7 and disease monitoring. 8 Currently, measurement of clinically adopted cancer protein biomarkers is mostly performed using affinity-based techniques.…”
Section: Introductionmentioning
confidence: 98%
“…Glycosylation is an important post-translational modification (PTM) mechanism of proteins, which modulates the protein function and is implicated in protein folding, trafficking, and cell-to-cell communications . Dynamic changes in glycosylation states have been associated with different disease processes, such as cancer, viral infection responses, and Alzheimer’s disease; the extent of the glycosylation could be associated with the disease progression and prognosis . These observed associations indicate that the specific glycosylation states of proteins can be utilized as biomarkers for clinical diagnosis and disease monitoring .…”
Section: Introductionmentioning
confidence: 99%
“…Protein glycosylation is involved in almost all biological processes, such as protein-protein interaction, cell signaling, and immune response. 1,2 Abnormal glycosylation oen accompanies the occurrence and development of diseases, 3 such as autoimmune diseases, 4 diabetes, 5 cardiovascular diseases, 6 inammatory diseases, 7 viral infection, 8,9 neurodegenerative diseases, 10,11 and cancers. [12][13][14][15] Deciphering disease-specic glycosylation is an effective strategy to uncover the underlying causes of various diseases and identify biomarkers for diagnosis and prognosis.…”
Section: Introductionmentioning
confidence: 99%